Systematic review and meta‐analysis of wound drains after thyroid surgery. Issue 5 (April 2014) - Woods, R. S. R.; Woods, J. F. C.; Duignan, E. S.; Timon, C.
<x xml:space="preserve">Abstract</x> Background Drainage after routine thyroid and parathyroid surgery remains controversial. However, there is increasing evidence from a number of randomized clinical trials (RCTs) suggesting no benefit from the use of drains. Methods A systematic review and meta‐analysis was performed according to PRISMA guidelines. A literature search was carried out, and RCTs comparing the use of drains versus no drains in patients who underwent thyroid or parathyroid surgery were included. Trials including patients who underwent lateral neck dissection were excluded. Methodological quality was graded and data were extracted by independent reviewers. Risk ratio (RR) or mean difference (MD) with 95 per cent confidence interval (c.i.) was calculated and heterogeneity was assessed. Results Twenty‐five RCTs were included in the meta‐analysis comprising 2939 patients. There was no significant difference between the two groups in rate of reoperation for neck haematoma (RR 1·90, 95 per cent c.i. 0·87 to 4·14), ultrasound‐assessed fluid volume on day 1 after surgery (MD 2·30 (95 per cent c.i. –0·73 to 5·34) ml), wound collection requiring intervention (RR 0·64, 0·38 to 1·09) or not (RR 0·93, 0·66 to 1·30), transient voice change (RR 2·33, 0·91 to 5·96) and persistent recurrent laryngeal nerve palsy (RR 1·67, 0·22 to 12·51). Length of hospital stay was significantly greater in the drain group (MD 1·25 (0·83 to 1·68) days), as were wound infection rates (RR 2·53, 1·23 to 5·21) and pain score measure using a visual analogue scale from 1 to 10 on day 1 after surgery (MD 1·46 (0·67 to 2·26) units). Conclusion The results indicate that drain use after routine thyroid surgery does not confer a benefit to patients.